2008
DOI: 10.1016/j.drup.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan, CD44 and Emmprin: Partners in cancer cell chemoresistance

Abstract: Hyaluronan is not only an important structural component of extracellular matrices but also interacts with cells during dynamic cell processes such as occur in cancer. Consequently, interactions of hyaluronan with tumor cells play important cooperative roles in various aspects of malignancy. Hyaluronan binds to several cell surface receptors, including CD44, thus leading to co-regulation of signaling pathways that are important in regulation of multidrug resistance to anticancer drugs, in particular anti-apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 149 publications
4
146
0
1
Order By: Relevance
“…10 Previous reports and the present study have demonstrated that Bsg promotes hyaluronan production and subsequent ␣-SMA expression in fibroblasts. 25,49 In summary, Bsg is a multifunctional molecule engaged in hyaluronan production, MMP production, cell adhesion, and ␣-SMA induction in renal fibrosis. Intervention targeting Bsg would have multiple effects on the prevention of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Previous reports and the present study have demonstrated that Bsg promotes hyaluronan production and subsequent ␣-SMA expression in fibroblasts. 25,49 In summary, Bsg is a multifunctional molecule engaged in hyaluronan production, MMP production, cell adhesion, and ␣-SMA induction in renal fibrosis. Intervention targeting Bsg would have multiple effects on the prevention of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been reported that Bsg promotes hyaluronan production in tumor cells and fibroblasts, [23][24][25]49 we asked whether or not Bsg deficiency would affect hyaluronan production by MEF. We found that the expression of hyaluronic acid synthase 2, which biosynthesizes hyaluronan, was lower in Bsg Ϫ/Ϫ MEF even in the steady state ( Figure 6A).…”
Section: Bsg Contributes To Hyaluronan Synthesis On Tgf-␤ Stimulationmentioning
confidence: 99%
“…It should be pointed out that EMMPRIN levels have been shown to increase in glioma and correlate with tumor grade (Sameshima et al 2000). EMMPRIN has also been shown to increase hyaluronan and colocalizes with its receptor CD44 (Toole and Slomiany 2008). Given that Hyaluronan and CD44 are important players in the CNS and in gliomas (see section 3.4.1) EMMPRIN may play a significant role in glioma invasion.…”
Section: Mmps In Gliomamentioning
confidence: 99%
“…Because of these findings, the "hyaluronan system," including the synthases, hyaluronan receptors, and hyaluronidases, may indeed be developed into therapeutic strategies to treat cancer. 2,14 Of note, 4-MU is already used in patients as a musculotropic smooth muscle relaxant to treat nonspecific abdominal pain and as a cholagogue (Cholspasmin). Furthermore, 4-MU is advertised in the United States and Europe as a prescription-free "neutraceutical" product (Heparvit) for cancer patients.…”
Section: Clinical Perspective On P 2322mentioning
confidence: 99%